Legal Analysis of Property Transfer Regions in Supporting Government Governance the Good Ones in South Bolaang Mongondow Regency - Adati, Stefhan; Lahaling, Hijrah; Nusa, Apriyanto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the legal aspects of the transfer of regional property in order to support good governance in South Bolaang Mongondow Regency. The transfer of regional property is a form of regional asset management that must be carried out transparently, accountably, and in accordance with applicable laws and regulations. The research method used is a normative juridical approach with a case study in South Bolaang Mongondow Regency. The results of the study show that the transfer of regional property still faces various legal obstacles, including the lack of understanding of regional officials on the transfer procedure, as well as the lack of supervision and transparency in its implementation. This has an impact on the low effectiveness of good governance. Therefore, it is necessary to increase the capacity of human resources, improve technical regulations, and strengthen the supervisory mechanism to ensure that the transfer of regional property runs according to the principles of good governance. This research provides strategic recommendations to encourage the creation of cleaner, transparent, and accountable governance in South Bolaang Mongondow Regency.